PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN HANDPHONE MEREK SAMSUNG (STUDI PADA GERAI SAMSUNG DI MALL CIPUTRA SEMARANG) - Ina Yulfika Candra, 15.05.51.0179; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of brand image, product quality and promotion on the decision process for purchasing Samsung brand mobile phones (Study on Samsung Outlets at Mall Ciputra Semarang). This study uses primary data and secondary data with a method of collecting data with a questionnaire. Samples taken as many as 100 respondents, using the sampling technique in this study using purposive sampling that is taking samples with the criteria that is all consumers who are crushed by Samsung at Mall Ciputra Semarang. Methods of data analysis using multiple linear regression. The test results obtained that brand image has a positive and significant effect on the process of purchasing decisions, product quality has a positive and significant effect on the process of purchasing and promotion decisions does not have a positive and significant effect on the process of purchasing decisions.